ФІНАНСОВА СКЛАДОВА ДЕЦЕНТРАЛІЗАЦІЇ: СУЧАСНИЙ СТАН ТА ТЕНДЕНЦІЇ РОЗВИТКУ - Чечетова Н. Ф.; Чечетова-Терашвілі Т. М.; Лелюк Н. Є. (World Science, 2019)
The article analyzed the results of reform fiscal decentralization. Investigated the combined budget figures of communities that already have a direct relationship with the state budget. The state of intergovernmental relations. The main problematic aspects of fiscal decentralization reforms. Grounded key areas to improve the mechanism of fiscal adjustment and offered practical recommendations aimed at solving urgent problems of further implementation of reforms. Direction of future research is to assess the budgetary risks in the context of the reform of fiscal decentralization.